Ready-to-wear sexual politics: The semiotics of visibility on Wits Pride T-shirts - Milani, Tommaso M.; Kapa, Koki (Stellenbosch Papers in Linguistics Plus, 2015)
The aim of this article is to investigate T-shirts as semiotic tools of the politics of visibility, showing which role these sartorial artefacts may play in competing struggles for recognition in which gender and sexuality intersect with other axes of social categorisations. Drawing on a queer multimodal approach, the article offers an analysis of the four promotional T-shirts that were distributed each year between 2011 and 2014 by the Transformation and Employment Equity Office at the University of the Witwatersrand (Wits), Johannesburg, in the context of the annual Pride parade on campus. Our main argument is that changes over time in the design of Wits Pride T-shirts represent a shift both in what is claimed to be the main goal of campus sexual politics and in the proposed means to achieve such a goal. If one were to imagine that each T-shirt is a corporeal embodiment of Wits Pride, then this body has changed considerably in four years: from a gay man who is (supposedly) ashamed of voicing his sexual identity; into a camp though masculine figure that loudly urges to counter racial division within same-sex desire; into a more multifaceted individual who proudly carries their gender and sexual uniqueness; and finally, into an activist who, in tension with the complex intersections that underpin discrimination, is perhaps a little reluctant to foreground gender and sexuality at all.